Academic Engagement in Students: The Role of Lecturers' Social Support Mediated by Academic Self-Efficacy and Growth Mindset - Fakhrurrozi, Muhammad; Wahyu Rahardjo; Anugriaty Indah Asmarany; Johanna, Jesicca (Universitas Ahmad Dahlan, 2025)
Academic engagement is a critical topic within the field of educational psychology, particularly in the context of higher education, due to its far-reaching positive and negative implications. Among the key antecedents believed to shape academic engagement are lecturer social support, academic self-efficacy, and a growth mindset. This study aimed to examine the extent to which academic self-efficacy and a growth mindset mediate the relationship between lecturer social support and academic engagement. The research involved 451 undergraduate students from the Greater Jakarta area, utilizing path analysis as the primary data analysis technique. The findings revealed two main outcomes: (1) lecturer social support has a significant direct effect on academic engagement, and (2) academic self-efficacy and growth mindset do not serve as strong mediators in this relationship. These results highlight the importance of enhancing lecturer support and suggest the need for targeted interventions to strengthen students’ academic self-efficacy and growth mindset within higher education institutions.